Bioavailability of zinc and copper in biosolids compared to their soluble salts - Heemsbergen, D.; McLaughlin, M.; Whatmuff, M.; Warne, M.; Broos, K.; Bell, M.; Nash, D.; Barry, G.; Pritchard, Deborah; Penney, N. (Elsevier Science Ltd, 2010)
For essential elements, such as copper (Cu) and zinc (Zn), the bioavailability in biosolids is important from a nutrient release and a potential contamination perspective. Most ecotoxicity studies are done using metal salts and it has been argued that the bioavailability of metals in biosolids can be different to that of metal salts. We compared the bioavailability of Cu and Zn in biosolids with those of metal salts in the same soils using twelve Australian field trials. Three different measures of bioavailability were assessed: soil solution extraction, CaCl2 extractable fractions and plant uptake. The results showed that bioavailability for Zn was similar in biosolid and salt treatments. For Cu, the results were inconclusive due to strong Cu homeostasis in plants and dissolved organic matter interference in extractable measures. We therefore recommend using isotope dilution methods to assess differences in Cu availability between biosolid and salt treatments. Metals in biosolids are not necessarily less bioavailable than their soluble salt.